2011
DOI: 10.2527/jas.2010-2892
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selection for residual feed intake on feeding behavior and daily feed intake patterns in Yorkshire swine1

Abstract: Residual feed intake (RFI) is a measure of feed efficiency defined as the difference between observed and predicted feed intake based on average requirements for growth and maintenance. The objective of this study was to evaluate the effect of selection for decreased RFI on feeding behavior traits and to estimate their relationships with RFI. Three data sets from the 4th and 5th generations of a selection experiment with a line selected for reduced RFI (LRFI) and a randomly selected control line (CTRL) were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 14 publications
16
71
0
Order By: Relevance
“…The RFI value found in this experiment of −140 g/day is in line with previous experiments proving that the pigs in this study are a population of pigs divergent in RFI (Young and Dekkers, 2012). In contrast to previous RFI studies (Young et al, 2011;Mani et al, 2013;Montagne et al, 2014) backfat was not included in the model in this study. However, Do et al (2014) established a correlation coefficient of 0.96 between models with or without backfat, suggesting that the non-inclusion of backfat in this study will not unduly influence the results.…”
Section: Resultssupporting
confidence: 89%
“…The RFI value found in this experiment of −140 g/day is in line with previous experiments proving that the pigs in this study are a population of pigs divergent in RFI (Young and Dekkers, 2012). In contrast to previous RFI studies (Young et al, 2011;Mani et al, 2013;Montagne et al, 2014) backfat was not included in the model in this study. However, Do et al (2014) established a correlation coefficient of 0.96 between models with or without backfat, suggesting that the non-inclusion of backfat in this study will not unduly influence the results.…”
Section: Resultssupporting
confidence: 89%
“…In contrast, in a study with growing Yorkshire pigs selected for differences in residual feed intake, a similar bimodal pattern as was only found for the number of visits/2-h block along the day, but not for occupation time, was seen, which was constantly high between 1200 and 2000 h (Young et al, 2010). No sex differences or treatment differences were obvious in the diurnal pattern, but pronounced differences in feed intake behavior along the fattening period occurred.…”
Section: Discussionmentioning
confidence: 54%
“…Our results also suggest that low RFI is associated with shorter daily eating time and lower number of meals, in agreement with a larger study on these RFI lines at earlier stages of selection (Gilbert et al, 2009). In purebred Yorkshire pigs, Young et al (2011) reported no significant difference in feeding patterns between a low RFI line compared with a control line after five generations of selection, but a trend for low RFI to visit the SEF fewer times and to spend less time eating per visit. In our study, the line difference on feed intake and visit duration was larger at the end of the growing period, as given in the study by Gilbert et al (2009).…”
Section: Discussionmentioning
confidence: 93%
“…In pigs, some studies have focused on relationships between RFI and appetite and feeding activity (De Haer et al, 1993;Rauw et al, 2006;Gilbert et al, 2009;Young et al, 2011). They indicate that decreased RFI is † E-mail: marie-christine.salaun@rennes.inra.fr Animal (2014), 8:11, pp 1898-1906 animal 1898 related to diminished daily feed intake (DFI), feeding patterns characterized by fewer meals, less time eating per day and a higher feeding rate.…”
Section: Introductionmentioning
confidence: 99%